Spatial distribution of marine debris on the seafloor of Moroccan waters. Issue 1 (15th November 2017) - Loulad, S.; Houssa, R.; Rhinane, H.; Boumaaz, A.; Benazzouz, A.
Abstract: Marine debris pollution is considered as a worldwide problem and a direct threat to the environment, economy and human health. In this paper, we provide the first quantitative assessment of debris on the seafloor of the southern part of the economic exclusive waters of Morocco. The data were collected in a scientific trawl survey carried out from 5 to 25 October 2014 between (26N) to (21N) covering different stratums of depths (from 10 to 266 m) and following a sampling network of 100 stations distributed randomly in the study area. A total of 603 kg of debris was collected and sorted into five main categories: plastic, metal, rubber, textiles and glass. Over 50% of collected items was made by plastic, 94% of them are the plastic fishing gear used to capture the Octopus vulgaris . The analysis of the distribution shows that anthropogenic debris is present in the majority of the prospected area (∼ 47, 541 km 2 ) with different densities ranging from 0 to 1768 (± 298, 15) kg/km 2 . The spatial autocorrelation approach using GIS shows that the concentration of this debris is correlated very well with a set of factors such as the proximity to fishing activity sites. Moreover, the mechanism of transportation and dispersion was influenced by the hydrodynamic properties of the region. Highlights: The first quantitative assessment of marine debris on the seafloor of Moroccan waters. The mean density of collecting debris was ranging from 0 to 1768kg/km 2 . 83% of collecting items are formed by plastic, the majority of them are plastic pots used to catch Octopus vulgaris. Fishing activity likely has a strong effect on the accumulation of the debris. The hydrodynamic aspect of the area influenced the movement of debris to the south and to the ocean interior.